2010
DOI: 10.1002/ibd.21021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced muscle mass and bone size in pediatric patients with inflammatory bowel disease

Abstract: Reduced bone geometry was explained only in part by reduced height. Bone disease in children with IBD seems to be secondary to muscle wasting, which is already present at diagnosis. With longer disease duration, bone adapts to the lower muscle CSA. Serum albumin concentration is a good marker for muscle wasting and abnormal bone development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 36 publications
(42 reference statements)
4
59
1
3
Order By: Relevance
“…Bone and muscle parameters were measured by pQCT (XCT-2000 scanner; Stratec, Pforzheim, Germany) as described previously [20]. In brief, at the nondominant forearm, the scanner was positioned corresponding to 4 and 65% of forearm length, and at both sites 2-mm-thick single tomographic slices were measured with a voxel size of 0.4  mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone and muscle parameters were measured by pQCT (XCT-2000 scanner; Stratec, Pforzheim, Germany) as described previously [20]. In brief, at the nondominant forearm, the scanner was positioned corresponding to 4 and 65% of forearm length, and at both sites 2-mm-thick single tomographic slices were measured with a voxel size of 0.4  mm.…”
Section: Methodsmentioning
confidence: 99%
“…Bone parameters were analyzed as described previously [20] at baseline, week 4, 12, and 24 and included insulin-like growth factor 1 (IGF-1), insulin-like growth factor-binding protein 3 (IGF-BP), C-terminal propeptide of type I collagen (C1CP), bone-specific alkaline phosphatase (bsaP), intact parathyroid hormone (iPTH), desoxypyridinoline (DPD, urine), and 25-OH vitamin D. A 25-OH vitamin D level <10 ng/ml was considered as insufficient, between 10 and 20 ng/ml as deficient, and >20 ng/ml as normal. In addition, vitamin K status was assessed by measuring plasma phylloquinone (vitamin K1) and PIVKA-II (prothrombin produced in vitamin K absence) [23].…”
Section: Methodsmentioning
confidence: 99%
“…While both Dubner et al 58 and Bechtold et al 57 found that cortical vBMD in children with CD was not lower than that of control subjects, Liu et al 59 have shown that cortical vBMD is not significantly associated with mechanical properties (failure load, failure moment, and stiffness) in the tibia, but that total bone CSA and cortical CSA are associated with mechanical properties (i.e., periosteal and endosteal circumferences). Therefore, in terms of fracture risk reduction, cortical geometry, not cortical vBMD per se, is an important factor.…”
Section: New Assessment Techniquesmentioning
confidence: 95%
“…53 There are two studies that have investigated bone parameters using pQCT in children with CD. 57,58 Both studies have shown that trabecular vBMD is reduced in patients with CD compared with controls. It was reported by Dubner et al 58 that their patients were, on average, on the 10th percentile for trabecular vBMD for age, sex, and race, and that this was consistent with decreased bone formation, as a result of circulating inflammatory cytokines, and potentially, increased bone resorption.…”
Section: New Assessment Techniquesmentioning
confidence: 97%
“…Кроме того, дети с ВЗК особенно подвержены нару-шениям состояния костной ткани в связи с повышен- [14][15][16]. Тяжелую остеопению регистрируют у 3-6% детей с ЯК и у 12-18% пациентов с БК [14,[17][18][19].…”
unclassified